2013
DOI: 10.1109/lsp.2013.2263135
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Non-Local Means

Abstract: In this paper, we propose a so-called probabilistic non-local means (PNLM) method for image denoising. Our main contributions are: 1) we point out defects of the weight function used in the classic NLM; 2) we successfully derive all theoretical statistics of patch-wise differences for Gaussian noise; and 3) we employ this prior information and formulate the probabilistic weights truly reflecting the similarity between two noisy patches. The probabilistic nature of the new weight function also provides a theore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
2
55
0
Order By: Relevance
“…Recent studies in additive Gaussian noise reduction have shown that similarities between overlapping patches should be weighted using a dedicated kernel [52]. This idea could be extended to our SAR denoising method by adapting the kernel ψ.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in additive Gaussian noise reduction have shown that similarities between overlapping patches should be weighted using a dedicated kernel [52]. This idea could be extended to our SAR denoising method by adapting the kernel ψ.…”
Section: Discussionmentioning
confidence: 99%
“…NLM algorithm corrects the noisy image rather than separates the noise (oscillatory) from true image (smooth), as is the case of DWT. In recent years many variants of NLM have been developed as for example Probabilistic NLM (PNLM) (Wu et al, 2013).…”
Section: Non-local Meanmentioning
confidence: 99%
“…For example, Ville and Kocher (2009) suggest SUREbased optimization of parameters selection. In our research we took general values for the parameters as given in (Wu et al, 2013) …”
Section: Nlm Parametersmentioning
confidence: 99%
See 2 more Smart Citations